A Survey on Internet of Vehicle (IoV): A pplications & Comparison of VANETs, IoV and SDN-IoV (ELEKTRIKA- Journal of Electrical Engineering, 2021)
The swift evolution of communication network technologies brings the smart connected objects into existence. The objects or things are connected and able to communicate with each other through Internet of Things (IoT). Internet of Vehicle (IoV) are the subset of the IoT technologies that has been implemented to the vehicle. IoV is the evolution of traditional Vehicular Adhoc Networks (VANETs) bringing new technologies to the smart connected vehicles. IoV network communication is purposedly to serve a real time data exchanged on roads between the vehicles and roads, vehicles and vehicles, vehicle and sensors, and vehicles and everything through different network technologies. There are significant differences between IoV, SDN-IoV and VANETs in term of network architecture, features, and applications that available. IoV and IoV-SDN is using different network framework giving different flexibility and scalability. In term of features and applications, IoV and IoV-SDN are having more wider and broad wireless connection technology in contrast with VANETs. In this survey paper, the survey will focus on the introduction to SDN, and differences of application and features in IoV, SDN-IoV and VANETs.
Keywords: Internet of Vehicle (IoV), SDN, SDN-IoV, VANETs